The Relationship Between Observers' Self-Attractiveness and Preference for Physical Dimorphism: A Meta-Analysis - Chen, Lijun; Jiang, Xiaoliu; Fan, Huiyong; Yang, Ying; Ren, Zhihong (Frontiers in Psychology, 2018)
Background: Many studies have reported an association between observers’ self-attractiveness and their preference for sexual dimorphism across different physical domains, including the face, voice, and body. However the results of these studies are inconsistent. Here, a meta-analysis was conducted to estimate the association between observers’ own attractiveness and their dimorphic preference. Methods: Major electronic databases including PsycINFO, Web of Science, PubMed, ProQuest, and Google Scholar were searched during April 2017(the first time) and April 2018 (the second time). The effect size was calculated for masculine and feminine preferences respectively, and moderating effect analysis were conducted separately too. Results: We identified 5359 references, of which we included 25 studies (x = 55, x = number of the effect size) with 6853 participants in the meta-analysis. Across these studies, the correlation between observers’ own attractiveness and their sexual dimorphic preference was 0.095 (x = 55) and that for preference for masculinity (x = 39) and femininity (x = 16) was 0.102 and 0.076, respectively. The results of the funnel plot, Egger’s regression method, and fail-safe number suggested that there was no publication bias. The relationship depended on the measures of observers’ own attractiveness (subject or objective), preference task (attractiveness rating, forced-choice, face sequence test, or attractiveness rating and forced choice), relationship context (short or long term) and opposite or same sex (the gender of the observer and host). Furthermore, for female participants, using a hormonal contraceptive also influenced their masculinity preference. The effect size for the preference for a masculine body and voice was larger than that for facial masculinity. Conclusion: We found a small but significant correlation between self-attractiveness and physical dimorphic preference, and the relationship depends on observers’ gender, type of preference task, relationship context, measurement of observers’ attractiveness, and type of stimuli. Therefore, in future studies, researcher should consider these factors and their interactions.